You want me to do what? Two daily diary studies of illegitimate tasks and employee well‐being. (1st July 2015) - Eatough, Erin M.; Meier, Laurenz L.; Igic, Ivana; Elfering, Achim; Spector, Paul E.; Semmer, Norbert K.
Summary: Illegitimate tasks, a recently introduced occupational stressor, are tasks that violate norms about what an employee can reasonably be expected to do. Because they are considered a threat to one's professional identity, we expected that the daily experience of illegitimate tasks would be linked to a drop in self‐esteem and to impaired well‐being. We report results of two daily diary studies, one in which 57 Swiss employees were assessed twice/day and one in which 90 Americans were assessed three times/day. Both studies showed that illegitimate tasks were associated with lowered state self‐esteem. Study 1 demonstrated that high trait self‐esteem mitigated that relationship. Study 2 showed that illegitimate tasks were associated with not only lowered state self‐esteem but also lower job satisfaction and higher anger and depressive mood, but not anger or job satisfaction remained elevated until the following morning. Copyright © 2015 John Wiley & Sons, Ltd.